Evaluation Of Midwives' Compliance In Implementing The Principles Of Respectful Maternity Care In Antenatal Care Services At Community Health Centers - Cahyani, Mila; Surani, Endang (Jurnal Maternitas Kebidanan, 2025)
This study aims to comprehensively evaluate the level of midwives' compliance in implementing Respectful Maternity Care (RMC) principles in antenatal care (ANC) services at community health centers (Puskesmas), through a systematic and structured literature review approach. The literature search was conducted methodologically by utilizing three main, credible and broad-based scientific databases: Google Scholar, PubMed, and Publish or Perish. The search strategy was formulated using a combination of keywords in Indonesian and English, such as: "Respectful Maternity Care," "Midwives Compliance," "Antenatal Care," "Midwives Compliance," and "Respective Maternity Care," with publication restrictions for the period 2021 to 2025 to ensure data up-to-dateness. Of the 99 articles identified in the initial process, a strict selection stage was carried out based on inclusion criteria, namely articles with full-text access that specifically discussed midwives' compliance in implementing RMC principles in ANC services at the primary care level such as community health centers. This selection yielded five eligible and relevant articles for in-depth analysis. The analysis showed that the implementation of RMC principles, including empathetic and effective communication, protection of patient privacy and dignity, and transparent and understandable information delivery, significantly contributed to increased maternal satisfaction and encouraged their adherence to ANC procedures. Furthermore, structured training for health workers, particularly midwives, significantly improved the quality of RMC principles in the field. Therefore, it is recommended that regular evaluations of ANC service practices and the development of standardized, ongoing training programs be implemented. These efforts are crucial to ensure the delivery of antenatal care services based on professional ethics, upholding humanitarian values, and placing women at the center of attention in the maternal health care system.